Permanent fault identification for distribution network based on characteristic frequency signal injection using power electronic technology - Zhang, Zhihua; Liu, Jian; Ren, Biying; Ma, Yuan (Frontiers in Energy Research, 2022)
In order to identify the fault nature when phase-to-phase short circuit fault occurs in distribution lines and realize adaptive reclosing of distribution lines more accurately, a fault identification scheme using an inverter-based power electronic technology and power supply from stored energy capacitor is proposed in this paper. The corresponding device is designed which is composed of rectification, energy storage and inverters. Supplied by power from high voltage side of distribution transformers, three-phase symmetrical characteristic frequency voltage signals are injected into the de-energized network. Then the fault type can be determined according to the positive sequence resistance of the equivalent network under different fault properties. In this paper, the overall structure diagram of the system scheme is proposed, and the operation sequence of the system is analyzed. The control strategy is designed to maintain the stability of the output voltage. The feasibility and rationality of the proposed scheme are verified by theoretical analysis and simulation results.